Free software: An alternative to automate information units - Chinchilla Arley, Ricardo (2011)
The document describes the budgetary problem in the information units and the high costs of the commercial software specialized in the automation of libraries. It describes the origins of free software and its meaning. It mentions the three levels of automation within a library: catalog automation, repository generation and comprehensive automation. It points out the different free software applications for each of the levels and offers a series of advantages and disadvantages in the use of this type of products. It is concluded that the automation project is arduous but full of satisfactions, emphasizing that there is no project free of costs, because although it is true that free software is free, there are other costs related to the implementation, training and implementation of the project.